(untitled) (International Conference on Computing, Artificial Intelligence and Information Systems, 2026)
This study is aimed at developing a comprehensive information system for real-time monitoring of smart agroecosystems based on the noosphere concept, enhancing energy efficiency, and ensuring the security of IoT systems. The proposed system enables continuous measurement of environmental parameters, including soil moisture, water level, temperature, and mineralization, as well as visual monitoring through remote cameras, and data storage and processing on the Amazon Web Services (AWS) cloud platform.